Implementasi Sistem Monitoring Pada Rumah Jamur Menggunakan Jaringan Nirkabel Berbasis Protokol Komunikasi Message Queuing Telemetry Transport (MQTT) - Nugraha Pangestu; Rizal Maulana; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Nowadays, mushroom cultivations are growing rapidly in the society. Mushrooms have been becoming the popular groceries because of it's affordable price for all people. In it's growth process, Mushroom will need two main factors in order to grow properly; which are : temperature and humidity of the room. These two factors need to be controlled continuously to fit the ideal value limit. The ideal temperature for mushroom growth ranges between 25-30 â—‹C and the air humidity ranges between 60-90%. To overcome these problems, we proposed a system that can continuosly monitor temperature and humidity of mushroom house using MQTT protocol. To detect temperature and humidity, DHT-22 sensor is used. The sensor data will be processed by Arduino microcontroller and then sent using ESP8266-01 Wi-fi module which connected through the Wi-fi network to the Thingsboard server using MQTT protocol. Finally the data will be displayed in the form of charts and graphs. We evaluate the system using the delay test by calculating the time required by each sensor to process and read the data until the data is sent and displayed on the Thingsboard server. The results of delay test have confirmed that the system takes an average of 1.20 seconds in a single delivery of data to the Thingsboard server.